Keputusan Pembelian Berdasarkan Differensiasi Produk dan Word Of Mouth: Pengujian Empiris pada Industri Rumah Tangga 2R - Rosiawan, Rizky; Imanda, Reza Andika (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research seeks to analyze and test the influence of product differentiation and word of mouth on purchasing decisions. analyze and test the influence of product differentiation and word of mouth on buying decisions. This research uses quantitative methods. The population used in this research is 2R household industrial consumers whose numbers are infinite or unknown. The sampling method used in this research was an accidental sampling of 100 respondents. The data analysis method used in this research is Multiple Linear Regression Analysis, with the help of SPSS version 25. The results of this research show that: 1) Product differentiation has a positive effect on purchasing decisions. 2) Word of Mouth has a positive effect on purchasing decisions. 3) Product differentiation and Word of Mouth have a positive effect on purchasing decisions. Suggestions for companies are to develop 2R peanut-ting products and increase promotions.